Effect of colchicine on physiological and biochemical properties of Rhodococcus qingshengii - Yu. A. Markova; L. A. Belovezhets; V. N. Nurminsky; I. S. Kapustina; N. V. Ozolina; V. V. Gurina; A. L. Rakevich; A. V. Sidorov (Вавиловский журнал генетики и селекции)
The genus Rhodococcus includes polymorphic non-spore-forming gram-positive bacteria belonging to the class Actinobacteria. Together with Mycobacterium and Corynebacterium, Rhodococcus belongs to the Mycolata group. Due to their relatively high growth rate and ability to form biof ilms, Rhodococcus are a convenient model for studying the effect of biologically active compounds on pathogenic Mycolata. Colchicine was previously found to reduce biof ilm formation by P. carotovorum VKM B-1247 and R. qingshengii VKM Ac-2784D. To understand the mechanism of action of this alkaloid on the bacterial cell, we have studied the change in the fatty acid composition and microviscosity of the R. qingshengii VKM Ac-2784D membrane. Nystatin, which is known to reduce membrane microviscosity, is used as a positive control. It has been found that colchicine at concentrations of 0.01 and 0.03 g/l and nystatin (0.03 g/l) have no signif icant effect on the survival of R. qingshengii VKM Ac-2784D cultivated in a buffered saline solution with 0.5 % glucose (GBSS). However, colchicine (0.03 g/l) signif icantly inhibits biof ilm formation. Rhodococcus cells cultivated for 24 hours in GBSS with colchicine acquire a rounded shape. Colchicine at 0.01 g/l concentration increases C16:1(n-7), C17:0, C20:1(n-9) and C21:0 fatty acids. The microviscosity of the membrane of individual cells was distributed from the lowest to the highest values of the generalized laurdan f luorescence polarization index (GP), which indicates a variety of adaptive responses to this alkaloid. At a higher concentration of colchicine (0.03 g/l) in the membranes of R. qingshengii VKM Ac-2784D cells, the content of saturated fatty acids increases and the content of branched fatty acids decreases. This contributes to an increase in membrane microviscosity, which is conf irmed by the data on the GP fluorescence of laurdan. All of the above indicates that colchicine induces a rearrangement of the Rhodococcus cell membrane, probably in the direction of increasing its microviscosity. This may be one of the reasons for the negative effect of colchicine on the formation of R. qingshengii VKM Ac-2784D biof ilms.